Ten Steps Toward Improving In-Hospital Cardiac Arrest Quality of Care and Outcomes - Nallamothu, Brahmajee K.; Greif, Robert; Anderson, Theresa; Atiq, Huba; Couto, Thomaz Bittencourt; Considine, Julie; De Caen, Allan R.; Djärv, Therese; Doll, Ann; Douma, Matthew J.; Edelson, Dana P.; Xu, Feng; et al. (Circulation: Cardiovascular Quality and Outcomes, 2023)
Improving in-hospital cardiac arrest (IHCA) quality of care for adult and pediatric patients—not simply survival—requires a comprehensive set of programs and actions. Ideally, these should be embedded in a system of care that (1) plans and prepares for IHCA, (2) prevents IHCA when avoidable, (3) delivers high-quality, guidelinebased resuscitation, and (4) continuously evaluates and improves itself within a culture of person-centered care.
Keywords: Adult; Cardiopulmonary resuscitation; Child; Humans; Incidence; Sudden cardiac arrest; Survival rate